Characterization of the ceramic Glazed tiles of the Palácio Almada (Lisboa) - Flor, Pedro (2012)
This study reports the mineralogical and chemical characterization of the ceramic body of tiles signed by Gabriel del Barco, which belong to the Palácio Almada in Lisbon [1]. Nowadays, the tile panels are not in its original place and their appearance reflect the constant changes that they have been through. Gabriel del Barco was an important tile painter from the 17th century, who began his career as an oil painter, linked to the most relevant Portuguese baroque artists. The influent Almada family was the owner of the former palace near Rossio, one of the most significant and busy squares in 17th century Lisbon. Gabriel del Barco has been currently under investigation by the authors of this presentation through a FCT funded project [2]. In fact, the painter’s characteristics and his large amount of works (both signed and ascribed), make him a unique artist in the Portuguese tile’s panorama. Powder samples carefully removed from the two panels of the palace were analysed by X-ray diffraction (DRX) and energy-dispersive X-ray spectroscopy (EDS). The results revealed that the mineralogical and chemical compositions are almost the same for the two panels. Chloride is present only in one of the panels. A comparison with the present results is made with a recent work, where signed and nonsigned tiles attributed to the artist, was made [3]. We discuss the several factors that may affect the characteristics of old tiles, which may involve differences in the manufacturing process, or environmental factors as the precipitation of water